Impact of COVID-19 on the epidemiological profile of Heart Failure (HF) in the 10th Regional of Paraná (Research, Society and Development, 2025)
This study aimed to analyze the impact of the COVID-19 pandemic on the epidemiological profile of Heart Failure (HF) in the 10th Health Region of Paraná. It is a descriptive, cross-sectional, retrospective and documentary study based on DATASUS data, with a quantitative approach (Pereira, 2018). Descriptive statistics were used with averages and absolute and relative frequencies (Shitsuka et al., 2014). The analysis covered data such as hospitalizations, deaths, mortality rates, average hospital stay and cost per patient between 2018 and 2024. A drop in hospitalizations and a rise in mortality rate were observed during the pandemic. Post-pandemic data showed a gradual recovery. It is concluded that the pandemic significantly affected the management of HF, highlighting the importance of continuous care strategies.